2016
DOI: 10.2485/jhtb.25.181
|View full text |Cite
|
Sign up to set email alerts
|

Bone and Gingival Connective Tissue Responses towards Nanosecond-Pulsed Laser-Treated Titanium Implants

Abstract: :The aim of this study was to evaluate bone and gingival connective tissue responses towards nanosecond-pulsed laser-treated titanium implants. A Nd:YVO 4 nanosecond-pulse laser with a defocus technique was used to modify the surfaces of two types of cylindrical titanium implants. One had a 3.5 mm diameter and 7.0 mm length ( 3.5 Ti) to assess rabbit bone responses; the other a 1.0 mm diameter and 4.5 mm length ( 1.0 Ti) to assess rat gingival connective tissue responses. Laser-treated titanium implants, a 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…The zirconia implants were placed according to previously described methods [44,48]. In a previous study, screw-type or cylinder-type titanium implants were inserted into the sockets of the maxillary molars of rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The zirconia implants were placed according to previously described methods [44,48]. In a previous study, screw-type or cylinder-type titanium implants were inserted into the sockets of the maxillary molars of rats.…”
Section: Discussionmentioning
confidence: 99%
“…The implants were inserted into the sockets of the extracted maxillary teeth of rats, as described by earlier reports [44,48]. Surgery was conducted under general anesthesia administered by an intraperitoneal injection of ketamine hydrochloride (47 mg/kg, Daiichi Sankyo Propharma Co., Ltd. Tokyo, japan) and medetomidine hydrochloride (0.4 mg/kg, Nippon Zenyaku Kogyo Co., Ltd. Fukushima Japan).…”
Section: Animal Experiments For Zirconia Implantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The attachment of gingival connective tissue to implant materials is unsatisfactory compared with its tight bonding to bone. Fukayo et al 17) evaluated the attachment of gingival connective tissue to nanosecondpulsed laser-treated titanium implants in the rat maxilla. Polarized light microscopic observation revealed perpendicular rod-like attachments of gingival collagen fibers on the laser-treated titanium implant surface.…”
Section: Discussionmentioning
confidence: 99%
“…Nanosecond-pulse laser irradiation can alter not only the surface morphology and roughness but also the condition of the titanium oxide layer by heat input, resulting in better cytocompatibility 15,16) . Fukayo et al 17) evaluated tissue response towards nanosecondpulsed laser-treated titanium after implantation into the tibiae of rabbits or the extracted sockets of rat maxillary molars. They found that nanosecond-pulsed laser treatment resulted in improved bone responses and attachment of gingival connective tissue.…”
Section: Introductionmentioning
confidence: 99%